Diversity of hydrozoans on artificial substrates in large commercial ports of the Sea of Marmara - Yüksel Esin; Isinibilir Melek; Martell Luis (Oceanological and Hydrobiological Studies)
Research on biofouling assemblages in large ports is crucial for economic, environmental and regulatory purposes, as it provides critical information for managing marine ecosystems, preventing the spread of invasive species and developing effective antifouling strategies. Hydrozoans are among the most common invertebrates found in marine biofouling communities, making them a priority taxon for monitoring and identification in large ports. In this study, we documented the diversity of benthic hydrozoans growing on three types of artificial panels (wood, plastic, and rope) submerged for three months in the major commercial ports of Ambarli, Haydarpasa, Kocaeli, and Bandirma, located in the Sea of Marmara. Seven species of hydrozoans (Ectopleura crocea, Obelia dichotoma, Bougainvillia muscus, Clytia gracilis, Eudendrium capillare, Eudendrium merulum and Sertularella ellisii) were observed throughout the study. Unique fouling hydrozoan assemblages were identified in each port, regardless of the type of panel used, suggesting that differences in the pool of species available for recruitment and port-specific conditions have a greater impact on the structure of local fouling assemblages than the type of substrate. Ectopleura crocea, a species typical of artificial substrates and characterized by high invasive potential, was recorded for the first time in the Sea of Marmara during this study.